Comprehensive Physiology 2014
DOI: 10.1002/cphy.c140030
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoneural and Adrenomedullary Responses to Mental Stress

Abstract: This concept-based review provides historical perspectives and updates about sympathetic noradrenergic and sympathetic adrenergic responses to mental stress. The topic of this review has incited perennial debate, because of disagreements over definitions, controversial inferences, and limited availability of relevant measurement tools. The discussion begins appropriately with Cannon's "homeostasis" and his pioneering work in the area. This is followed by mental stress as a scientific idea and the relatively ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 294 publications
(272 reference statements)
2
73
1
3
Order By: Relevance
“…Numerous cross-sectional and longitudinal studies have been conducted to explore the associations between cardiovascular reactivity to acute mental stress and hypertension (7,24,41,46). A recent meta-analysis by Chida and Steptoe (11) showed that greater BP reactivity to acute laboratory mental stress was longitudinally associated with several adverse cardiovascular outcomes, including hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous cross-sectional and longitudinal studies have been conducted to explore the associations between cardiovascular reactivity to acute mental stress and hypertension (7,24,41,46). A recent meta-analysis by Chida and Steptoe (11) showed that greater BP reactivity to acute laboratory mental stress was longitudinally associated with several adverse cardiovascular outcomes, including hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…First, MSNA responsiveness to mental stress can be widely variable in humans (7). Second, although early evidence suggested that self-perceptions of stress might explain the large interindividual variability associated with MSNA reactivity to mental stress (4), more recent studies have challenged this paradigm (6,9).…”
Section: Subjects With a Family History Of Hypertension (Fhh) Demonstmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this early work, a number of studies have been published that support the idea that MSNA responsiveness to mental stress is subject to inter‐individual variability (Carter & Ray, ; Fonkoue & Carter, ; Donadio et al . ), as highlighted by Carter & Goldstein () in their recent review. Carter & Ray () reported that when individuals were divided into groups according to their MSNA burst frequency response to mental stress (i.e.…”
Section: Introductionmentioning
confidence: 89%
“…However, previous studies have shown that greater chronic and acute psychological stress are also associated with heightened systemic inflammation (Rohleder et al, 2014) and affect the ANS (Carter and Goldstein, 2015; Nater et al, 2013). Cardiovascular reactions to laboratory stressors have been found to be consistent within an individual over time (Debski et al, 1993; Kamarck et al, 1992), raising the possibility that these responses may influence chronic inflammation.…”
Section: 0 Introductionmentioning
confidence: 97%